Domestic Waste Management Feasibility Study at Ahmad Dahlan University - Surahma Asti Mulasari; Asep Rustiawan (Intelektual Pustaka Media Utama, 2018)
Garbage dumped untreated into the environment causes health problems. As an educational institution, college should make waste management as a media in educating students in particular, and society. The purpose of this research is to open up new insights into what can be done by Universitas Ahmad Dahlan (UAD) to educate citizens (academics) on the responsibility of managing the environment, especially the waste management practice in college as well as a form of UAD concern for environmental sustainability. This study is a qualitative research which uses road grass analysis approach. Techniques of data retrieval is in-depth interviews with cleaning service, students, employees, canteen vendors, head of BIFAS, vice chancellor II, and the Head of Household. The problems that occurred include: unsorted garbage bins resulting in unpleasant odor, lowered aesthetics, comfort decrease in GARBAGE DUMP , improper behavior of UAD campus residents related to littering, and lack of specific policies related to waste management in campus. Problems of campus trash includes: absence of waste separation process which results in odor, lowered aesthetics, and comfort decrease in GARBAGE DUMP . Another problem is the improper behavior of residents of UAD campus associated with littering, and the lack of specific policies related to campus waste management.